(untitled) (Nordic Journal of African Studies, 2009)
This paper problematizes the manner in which health education messages, especially HIV/AIDS messages in sub-Saharan Africa, are transmitted to the population. It challenges the top-down method of disseminating health education information and suggests a culturally sensitive and relevant bottom-up approach. Culture consideration in message construction and cultural context decoding is supported by Airhihenbuwa (1995); Dutta-Bergman (2004, 2005). Complicating the situation further is the hegemonic masculinity that characterizes most cultures in the sub-region. Thus we contend that alternatives to health education should bring men on board in partnership with women as agents of change to reduce the spread of HIV/AIDS. The article adopts an approach of a critical literature review augmented by interview data from eight media practitioners. Some pragmatic solutions are put forth.